From soil to health: advancing regenerative agriculture for improved food quality and nutrition security - Rosier, Carl L.; Knecht, Anya; Steinmetz, Jasia S.; Weckle, Amy; Bloedorn, Kelly; Meyer, Erin (Frontiers in Nutrition, 2025)
Industrial agriculture practices including herbicide-pesticide usage, synthetic fertilizer application, large-scale monocropping, and tillage contribute to increasing concentrations of atmospheric carbon dioxide (CO2), exacerbating the effects of global climate change, damaging vital water resources via nutrient pollution and soil erosion, and significantly reducing biodiversity across ecosystems. Observed decadal declines in diet quality driven by industrial farming practices have led to a global health epidemic marked by increased micronutrient deficiency and malnutrition. Additionally, global incorporation of processed foods, a mechanism bolstered by the industrial agricultural complex, contributes to increased prevalence of non-communicable diseases (NCDs), including diabetes and obesity. Regenerative agriculture represents the latest farm management strategy to challenge industrial agricultural methodologies, offering potential approaches to mitigate the myriads of challenges associated with global agricultural food production. However, more than 40 years after redefining a millennium of Indigenous philosophies, numerous barriers continue to limit its large-scale adoption beyond 1% of global farmed acreage. Associated barriers include an unresolved operational definition, lack of standardized certification, and limited research to support both producers and extension specialists. A shortage of systemic collaborative support, including consumer interest and demand, hinders regenerative agriculture adoption. This review examines the global challenges posed by the industrial agriculture model, particularly regarding ecosystem degradation and an inability to meet human nutritional needs. We specifically evaluate the potential of regenerative agriculture to restore global ecosystem services, meet the demands of a growing population, and highlight key knowledge gaps requiring further investigation. Lastly, we identify policy initiatives that, if thoughtfully implemented, could significantly expand the acreage managed under regenerative practices.